2019
DOI: 10.1111/cdoe.12445
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and behaviours of people living with Multiple Sclerosis in Australia

Abstract: Objectives The literature describing the oral health of people with Multiple Sclerosis (MS) is scant and the findings equivocal. The aim of this study was to describe the oral health and oral self‐care behaviours of people living with MS and compare it to the Australian population. Methods Participants enrolled with the Australian MS Longitudinal Study (AMSLS) were invited to participate in the survey using an online or paper‐based questionnaire. Data were collected on level of disability, oral health, oral se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…For the three studies that did not include a control group, moderate to heavy plaque deposits were reported by more than 60.0% of people with multiple sclerosis in one, and a score of 1.30 was reported on the Plaque Index by Silness and Loe in another, indicative of only fair oral hygiene . Finally, in the third study, approximately one‐fifth of a large cohort of people with multiple sclerosis (22.1%) rated their oral health status as fair or poor, which was higher than figures reported in a large national survey of oral health (16.4%) . Taken together, there is suggestive evidence that multiple sclerosis may be associated with poorer oral hygiene.…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…For the three studies that did not include a control group, moderate to heavy plaque deposits were reported by more than 60.0% of people with multiple sclerosis in one, and a score of 1.30 was reported on the Plaque Index by Silness and Loe in another, indicative of only fair oral hygiene . Finally, in the third study, approximately one‐fifth of a large cohort of people with multiple sclerosis (22.1%) rated their oral health status as fair or poor, which was higher than figures reported in a large national survey of oral health (16.4%) . Taken together, there is suggestive evidence that multiple sclerosis may be associated with poorer oral hygiene.…”
Section: Resultsmentioning
confidence: 70%
“…The diagnosis of multiple sclerosis (reported in 13 of the 17 studies) was established using a range of standardized criteria: McDonald criteria (seven studies), Schumacher criteria (one study) and Poser criteria (one study). The International Classification of Diseases (ICD) criteria formed the basis for multiple sclerosis diagnosis in one study, while three other studies used medical reports (provided by physicians and neurologists), without mentioning the specific diagnostic criteria used . Four studies did not mention the classification used for diagnosis of multiple sclerosis .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations